Wounds: Militarized nursing, feminist curiosity, and unending war. (September 2019) - Enloe, Cynthia
Taking wartime nurses – and post-war nursing – seriously makes one think more politically about the wounds endured in wartime and what counts as a wartime 'wound'. Thinking about wounds and the wounded, in turn, reveals how war-waging officials, and militarizers more generally, have tried in the past, and today still try, to shrink citizens' awareness of militarism's negative consequences. Nursing, nurses, wounds, and the wounded each continues to be gendered, influencing the workings of both masculinities and femininities in past and current wartimes and post-war politics. Feminist analysts have expanded the 'political' and multiplied 'political thinkers'. Failing to absorb these feminist theoretical insights fosters the trivialization of nurses and other caretakers of the wartime wounded and their diverse political thinking. It is a failing with serious implications. Overlooking nurses and others who provide wartime care, combined with a lack of curiosity about wounds, perpetuates militarization and war.